Technological features in obtaining highly effective hydrogel dressings for medical purposes - Grytsenko, Oleksandr; Pokhmurska, Anna; Suberliak, Sofiia; Kushnirchuk, Mykola; Panas, Marta; Moravskyi, Volodymyr; Kovalchuk, Roman (Eastern-European Journal of Enterprise Technologies, 2018)
The new technology of formation of hydrogel dressings for medical purposes, containing particles of silver was developed. To obtain metal-containing composite hydrogels, we proposed a high-tech single-stage method, which involves polymerization of polymer-monomer compositions based on polyvinyl-pyrrolidone and 2-hydroxyethylmethacrylate with simultaneous chemical reduction of silver ions from its nitrate by ethanol. It was found by the thermometric research that the temperature conditions needed for chemical reduction of silver ions are achieved due to the heat, which is released at the exothermic polymerization reaction. The temporal and temperature parameters of polymerization depending on the composition of the original polymer-monomer composition, the content of solvent and of the initiator, and silver nitrate concentration were determined. They include the initial temperature of polymerization, maximum exothermic temperature, the time of reaching the maximum exothermic temperature, and duration of effect gel. The use of combined initiating system of iron (II) sulfate + benzoyl peroxide makes it possible to implement the process of obtaining hydrogels, containing silver particles, at room temperature, in the open air. The synthesis is technologically simple and is executed without complicated apparatus design. The authors proposed a new technology of formation of hydrogel films with the use of the centrifugal method. Polymerization with silver deposition occurs in the centrifugal form simultaneously with film formation, which allows obtaining the materials with predictable properties that have a uniform distribution of the filler with equal thickness and high quality surfaces in the polymer matrix. The film products obtained as a result of the developed technology can swell in water and other polar solvents, are characterized by durability, elasticity, bactericidal and antifungal properties. The results of the clinical studies showed sufficient clinical effectiveness of using the developed hydrogel dressings for medical purposes based on hydrogels, containing silver particles. Such materials in combination with the integrated therapy help to increase the speed and intensity of treatment of trophic venous ulcers of lower limbs